2013
DOI: 10.1179/1476830512y.0000000048
|View full text |Cite
|
Sign up to set email alerts
|

A novel insight on chronic AlCl3neurotoxicity through IL-6 and GFAP expressions: Modulating effect of functional food fenugreek seeds

Abstract: In the context of recent researches, IL-6 hypoproduction in the posterior brain could be a novel mechanism of Al chronic toxicity with a direct effect on glial cells. Using FSP as a diet supplement could offer a neuroprotective effect against Al toxicity. This could be mediated by astroglial cells protection, antioxidant and immunomodulatory actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In Mohammad‐Sadeghipour et al's study on fructose‐fed rats found that administration of 4‐week hydro‐Alcoholic extract of fenugreek seed contributed to increasing serum TAC levels and MDA reduction (Mohammad‐Sadeghipour et al, 2020). Furthermore, fenugreek seed powder was able to enhance IL‐6 expression and modulate pro‐oxidant‐related effects in Wistar rats that exposed to chronic aluminum (Belaïd‐Nouira et al, 2013). The antioxidant effects of fenugreek seed extract is due to the therapeutic roles of its phenolic content and active phytochemical components, including trigonelline, gitogenin, tigogenin, and yamogenin diosgenin choline (Choudhary & Yousuf, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In Mohammad‐Sadeghipour et al's study on fructose‐fed rats found that administration of 4‐week hydro‐Alcoholic extract of fenugreek seed contributed to increasing serum TAC levels and MDA reduction (Mohammad‐Sadeghipour et al, 2020). Furthermore, fenugreek seed powder was able to enhance IL‐6 expression and modulate pro‐oxidant‐related effects in Wistar rats that exposed to chronic aluminum (Belaïd‐Nouira et al, 2013). The antioxidant effects of fenugreek seed extract is due to the therapeutic roles of its phenolic content and active phytochemical components, including trigonelline, gitogenin, tigogenin, and yamogenin diosgenin choline (Choudhary & Yousuf, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its anti-diabetic remedy 23 , 24 , extracts of fenugreek seeds also display neuroprotective properties 25 , beneficial effect on Parkinson’s disease 26 , 27 and anti-inflammatory effects 28 , 29 in disease animal models. The action of N55 is consistent with the current trials of GLP-1 analogues in treatment of psoriasis 30 , Alzheimer’s disease 31 and Parkinson’s disease 32 .…”
Section: Discussionmentioning
confidence: 99%